Correlation of the AKT/mTOR signaling pathway with the clinicopathological features and prognosis of nasopharyngeal carcinoma - Yan Wang (PAGEPress Publications, 2021)
The primary aim of this study was to examine the correlation of the AKT/mTOR signaling pathway with the clinicopathological features and prognostic significance in nasopharyngeal carcinoma (NPC). The study tissues were collected from 285 patients with NPC and normal mucosal tissues were obtained from 289 individuals with normal nasopharynxes. Immunohistochemical staining was used to detected the expression of the AKT, mTOR, and p70 ribosomal S6 kinase (P70S6K) proteins. Follow-up was performed for between 8 and 60 months. Spearman’s rank correlation analysis was performed to evaluate the correlation of the expression of the AKT, mTOR, and P70S6K proteins in NPC tissues. Kaplan-Meier curves were plotted to show the survival of patients with NPC. A Cox proportional hazards model was used to explore the independent risk factors for prognosis. The expression of the AKT, mTOR, and P70S6K proteins in NPC tissues was higher than that in healthy nasopharyngeal mucosal tissues, and was correlated with T-staging, N-staging, clinical stage, distant metastasis, and differentiation. The positive expression of the AKT, mTOR, and P70S6K proteins was higher in patients with stage III/IV NPC, low differentiation, and metastasis. The survival rates of patients with NPC with AKT-positive, mTOR-positive, and P70S6K-positive expression were considerably lower than those without the expression of these proteins. Distant metastasis and the overexpression of the AKT, mTOR, and P70S6 proteins were independent risk factors for the prognosis of patients with NPC. The results obtained from this study indicated an association between the AKT/mTOR signaling pathway and the progression of NPC. The upregulation of the AKT/mTOR pathway in patients with NPC is a predictor of poor prognosis.